2021
DOI: 10.1111/jfbc.14044
|View full text |Cite
|
Sign up to set email alerts
|

Roasting intervention for the volatile composition of three varieties of nuts originating from Torreya yunnanensis

Abstract: Torreya (Torreya grandis cv. Merrillii), also known as Chinese Torreya, is an evergreen tree in the genus Taxus that has been cultivated for more than 1300 years in China (Dai et al., 2005). Among them, Torreya yunnanensis (Torreya Arn genus), as an excellent afforestation tree in northwestern Yunnan, has been listed as a national second-level protected plant in China (Li et al., 2016).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Zhang et al [11] identified 211 volatile components in green tea using GC×GC-TOF-MS, which is approximately 6.4 times more than that identified by GC-IMS. A total of 126 volatile components were detected in nuts by GC×GC-TOF-MS, approximately three times higher than that identified by GC-MS [12]. However, no information is available on the influence of pesticides on the VOC profile of strawberries.…”
Section: Introductionmentioning
confidence: 91%
“…Zhang et al [11] identified 211 volatile components in green tea using GC×GC-TOF-MS, which is approximately 6.4 times more than that identified by GC-IMS. A total of 126 volatile components were detected in nuts by GC×GC-TOF-MS, approximately three times higher than that identified by GC-MS [12]. However, no information is available on the influence of pesticides on the VOC profile of strawberries.…”
Section: Introductionmentioning
confidence: 91%